The relationship between moral distress and clinical care quality among nurses: an analytical cross-sectional study - Fateme Safari; Ali MohammadPour; Mahdi BasiriMoghadam; Alireza NamaeiQasemnia (BMC, 2024)
Abstract Background Nurses constitute the largest group of service providers in the healthcare system and significantly influence the quality of healthcare services. Factors such as ethical considerations may be related to the quality of care. This study aimed to determine the relationship between moral distress and the quality of clinical care among nurses working in Gonabad, Iran. Methods An analytical cross-sectional study was conducted on 252 nurses working in emergency, internal medicine, surgery, psychiatry, critical care and maternity wards at Allameh Bohlool Hospital from May to July 2023. This research used demographic information questionnaire, the revised Moral Distress Scale (MDS-R), and the Quality Patient Care Scale (QUALPAC). The significance level for the study was set at p < 0.05. Results There was a significant relationship between the frequency of moral distress and the quality of clinical care (p = 0.032), as well as between the intensity of moral distress and the quality of clinical care (p = 0.043). Nurses who experienced moral distress more frequently and intensely provided better quality care. However, there was no significant relationship between the effect of moral distress and the quality of clinical care (r = 0.032, p = 0.619). Additionally, a significant statistical relationship was found between the intensity of moral distress and the physical dimension of clinical care quality (r = 0.171, p = 0.007), indicating that increased moral distress intensity was associated with higher quality of physical care. Conclusions Nurses who experience higher levels of moral distress, both in terms of frequency and intensity, perform better in the care they provide and deliver it in the best possible manner, particularly in the physical dimension of care.